Portable mud remover - Kadir, Mohd Faiz; Harun, Mohd Zaim; Hassan, Mohd Fahrul; Hamdan, Nur Izzah; Paimin, Noor Farzee; Abdullah, Nor Sharifhatul Adila (Penerbit UTHM, 2017)
Basically, the only way to remove mud is by using shovel. The process of removing mud usually need us to shovel out the mud, put it into buckets and carry it outside and by using a garden sprayer or hose to wash away mud from hard surfaces [1]. This is because there are no specific tools or products to remove the mud in our industries. In that case, our group had come up with an idea to design a “Portable Mud Remover” which is inspired from a lawnmower and vacuum as shown in Figure 10.1. The idea of using concept of lawnmower is because to make is the product is portable and easy to handling. The smallest types of lawnmower are pushed by a human user and are suitable for small space. The problem occurs for the pool vacuum is that the product is not suitable to suck the mud because it is not designed for a heavy duty work.